Evaluasi Kapasitas Drainase Jalan Kebun Agung Menuju Gunung Kapur 2 Kota Samarinda - Suratmi; Suharto; Putra Wisnu Kusuma (Institut Teknologi Garut, 2026)
The Kebun Agung Road to Gunung Kapur segment in Samarinda City frequently experiences water ponding during periods of high rainfall intensity. This condition is caused by the existing drainage system not functioning optimally. Such conditions negatively affect traffic flow, road pavement structural integrity, and road user safety. This study aims to assess the capacity of the existing drainage channels to accommodate rainwater discharge. The approach used includes hydrological and hydraulic analysis. Rainfall data processing was carried out using the Gumbel Distribution and Log Pearson Type III Method to obtain design rainfall values, while design discharge was calculated using the Rational Method. Furthermore, channel capacity evaluation was conducted based on field measurements of channel dimensions, flow patterns, and physical channel conditions. The results show that the capacity of the existing drainage channel is 6.128 m³/s for the 2-year return period and 6.561 m³/s for the 5-year return period. These values indicate that the drainage channel is still capable of accommodating the design discharge. Nevertheless, adjustments to channel dimensions in several sections and routine maintenance are still required to prevent sedimentation and blockages that may reduce the flow capacity of the channel.